A course in the large sample theory of statistical inference - Hall, W. J. (William Jackson); Oakes, David (Statistician) (Boca Raton, FL CRC Press, an imprint of Taylor & Francis Group, 2024)
"This book provides an accessible but rigorous introduction to asymptotic theory in parametric statistical models. Asymptotic results for estimation and testing are derived using the "moving alternative" formulation due to R. A. Fisher and L. Le Cam. Later chapters include discussions of linear rank statistics and of chi-squared tests for contingency table analysis, including situations where parameters are estimated from the complete ungrouped data. The book is based on lecture notes prepared by the first author, subsequently edited, expanded and updated by the second author. Some facility with linear algebra and with real analysis including "epsilon-delta" arguments is required. Concepts and results from measure theory are explained when used. Familiarity with undergraduate probability and statistics including basic concepts of estimation and hypothesis testing is necessary, and experience with applying these concepts to data analysis would be very helpful"--Provided by publisher.
Includes bibliographical references and indexes.
Keywords: Statistical hypothesis testing -- Asymptotic theory